Multiscale Origami Structures as Interface for Cells. Issue 52 (7th December 2015) - Angelin, Alessandro; Weigel, Simone; Garrecht, Ruben; Meyer, Rebecca; Bauer, Jens; Kumar, Ravi Kapoor; Hirtz, Michael; Niemeyer, Christof M.
Abstract: A DNA‐based platform was developed to address fundamental aspects of early stages of cell signaling in living cells. By site‐directed sorting of differently encoded, protein‐decorated DNA origami structures on DNA microarrays, we combine the advantages of the bottom‐up self‐assembly of protein–DNA nanostructures and top‐down micropatterning of solid surfaces to create multiscale origami structures as interface for cells (MOSAIC). In a proof‐of‐principle, we use this technology to analyze the activation of epidermal growth factor (EGF) receptors in living MCF7 cells using DNA origami structures decorated on their surface with distinctive nanoscale arrangements of EGF ligand entities. MOSAIC holds the potential to present to adhered cells well‐defined arrangements of ligands with full control over their number, stoichiometry, and precise nanoscale orientation. It therefore promises novel applications in the life sciences, which cannot be tackled by conventional technologies. Abstract : MOSAIC combines DNA micro‐ and nanostructures to present ligands to living cells on surfaces (see picture) with a full control over their stoichiometry and nanoscale orientation. This technology allows to address fundamental questions in cell signaling.